Analysis of Health Promotion Strategies for Treatment of Cervical Cancer at Awal Bros Hospital Pekanbaru Riau - Kristiani, Ekalia; Sitepu, Rahmadani (JURNAL KESMAS DAN GIZI (JKG), 2024)
Cancer is one of the main causes of death, as many as 8.2 million people die from cancer. According to GLOBOCAN data in IARC (2020), cervical cancer cases in Indonesia increased by 36,633 (17.2%) with 234,511 deaths. Cervical cancer generally attacks women aged 30-39 years. Symptoms of cervical cancer are post-coital bleeding, smelly vaginal discharge, vaginal bleeding continuously without stopping, pain in the genitals are reported as early symptoms of cervical cancer. The aim of this research is to analyze Health Promotion Strategies in the treatment of cervical cancer at Awal Bros Hospital Pekanbaru. This type of research is qualitative. The number of informants was 4 informants. The results of research conducted by the health promotion program at Awal Bros Hospital in Pekanbaru show a holistic and sustainable approach in overcoming the challenge of cervical cancer. By focusing on education and empowerment, as well as addressing identified obstacles, these efforts have had a positive impact in increasing awareness, treatment compliance and quality of life for patients affected by cervical cancer. However, there is still a need to continue evaluating and adapting to increase the effectiveness of the program and ensure better access for all patients. The health promotion (advocacy) strategy for cervical cancer treatment was carried out quite well through a lobbying process and outreach to various agencies, Awal Bros Hospital carried out this by building an individual atmosphere and building a group atmosphere. By increasing participation in early screening and ensuring continuity of treatment for optimal effectiveness in preventing cervical cancer. Awal Bros Pekanbaru Hospital implements a health promotion strategy for cervical cancer with a focus on empowerment and a personal approach to patients and their families.